(untitled) (Academia Science Repository, 2023)
The article describes the problems in learning musical works independently, the lack of skills and competencies in learning musical works independently as a result of low level of use of educational literature and internet resources in information resource centers, lack of skills in playing instruments, vocals, singing in a choir, insufficient musical literacy.